The Use of R290 As a Replacement For R404A in Block Ice Machines - Febiadisti, Vigasta; Nia Nuraeni Suryaman; Arifin Santosa; Aep Saepudin; Andri Setiawan (Universitas Muhammadiyah Sidoarjo, 2025)
This study evaluates the performance of R290 refrigerant as an alternative to R404A in block ice-making machines based on vapor compression cycles. The method used is a quantitative experimental approach with direct testing of compressor power, condenser power, evaporator power, and coefficient of performance (COP) parameters. Test results indicate that R290 has lower power consumption and a higher COP compared to R404A, with a COP of 3.22 (R290) versus 2.48 (R404A). Additionally, R290 has a significantly lower global warming potential (GWP), making it more environmentally friendly. The more stable and efficient thermodynamic performance of R290 supports its effectiveness as an economical and sustainable alternative refrigerant for modern cooling applications.